Analisis Yuridis Pemberian Label Halal di Setiap Produk Yang Beredar di Pasar Ekonomi Indonesia - Risval Gogou; Ahmad Burhan Hakim (HOKI : Journal of Islamic Family Law, 2025)
Indonesia as a country with the majority Muslim religion needs attention to food product that are free in the market, but also needs to be noted that the food consumed is healthy. Basically, the inclusion of halal labeling is not mondatory or voluntary, but if a manufacturer is found to falsify a label without a certificate being carried out, the producer will be sanctioned in accordance with the applicable laws or regulations. This is done so that people know clear and honest information about the products they buy in the market. In this thesis the author uses normative research methods. The purpose of this paper is to find out how to label and sanction what is imposed if the producer violates the provisions of halal certification and labeling. Related to the licensing of certification is the authority (MUI) through the (LPPOM MUI) and for labeling were carried out by (BPPOM) after obtaining the permit file from LPPOM MUI. Regarding the law on guarantee of halal product number 33 of 2014 still awaiting government regulations (PP) to be carried out in accordance with the laws of the Halal Product Guarantee Board (BPJPH) later after the PP is issued, the certification authority is at BPJPH.